The real effects of financial constraints: Evidence from a financial crisis - Campello, Murillo; Graham, John R.; Harvey, Campbell R. (Journal of Financial Economics, 2010)
We survey 1,050 Chief Financial Officers (CFOs) in the U.S., Europe, and Asia to directly assess whether their firms are credit constrained during the global financial crisis of 2008. We study whether corporate spending plans differ conditional on this survey-based measure of financial constraint. Our evidence indicates that constrained firms planned deeper cuts in tech spending, employment, and capital spending. Constrained firms also burned through more cash, drew more heavily on lines of credit for fear banks would restrict access in the future, and sold more assets to fund their operations. We also find that the inability to borrow externally caused many firms to bypass attractive investment opportunities, with 86% of constrained U.S. CFOs saying their investment in attractive projects was restricted during the credit crisis of 2008. More than half of the respondents said they canceled or postponed their planned investments. Our results also hold in Europe and Asia, and in many cases are stronger in those economies. Our analysis adds to the portfolio of approaches and knowledge about the impact of credit constraints on real firm behavior.